ANALISIS KEKUATAN STRUKTUR RANGKA MESIN PENGERING BAWANG MENGGUNAKAN PERANGKAT LUNAK ANSYS APDL 15.0 - Azwir Sofyan; Jean Glusevic; Achmad Jusuf Zulfikar; Bobby Umroh (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2019)
Typical technology for processing red onion affects the quality of red onion produced. The process of drying red onion is one of the important factors in producing the best quality of red onion. Environmentally friendly and easy operation and maintenance technology is the desired technology. In the process of engine design, the strength of the material and structure are the main factors of the building of the machine. Calculation with finite element method (FEM) is the best choice to obtain information on stress distribution on a machine structure. In this study, the calculation of the FEM method was assisted by Ansys APDL 15.0 software. The objectives of this study were: (1) calculation of the load on the tray structure, (2) the distribution of stress on the tray structure, seat, and frame for red onion dryers, and (3) analyzing the strength of the material using the Tresca and Energy Distortion methods. The input load comes from the weight of the tray and red onion. The analytical method used is the finite element method with the type of structural analysis and Beam 3Node 189 element type. Based on the FEM simulation results, the maximum stress that occurs in the tray is 1.22 MPa and the maximum deflection is 0.0055 mm. The maximum stress in the tray support structure is 33.25 MPa and the maximum deflection is 0.014 mm. The maximum stress on the frame structure of the onion drying machine is 0.89 MPa and the maximum deflection is 0.000235 mm which occurs in the middle of the machine structure. Using the Tresca and Distortion Energy theories, it is found that the stresses that occur are still far from the failure criteria for all structures. Likewise, the deflection that occurs is very small so that the construction of the onion drying machine is safe to use.